IMPLEMENTASI ETIKA KEGURUAN DALAM PERILAKU MENGAJAR - Relin Nelfi Yolanda; Suci Yuniati; Annisah Kurniati; Depriwana Rahmi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2024)
Ethics plays a crucial role for teachers in the classroom as it enables them to distinguish between right and wrong, behave politely and respectfully, and maintain good manners while teaching, which in turn enhances their professional prestige. Breaches of professional ethics by teachers can negatively impact students' learning, particularly in mathematics. Therefore, this study aims to explore and analyze the implementation of professional teaching ethics specifically among mathematics teachers. The research is conducted using a literature review method, gathering data from previously published national educational journals that align with the criteria and theme related to teaching ethics in the classroom. The data is analyzed descriptively to identify key aspects and practices of ethical behavior during instruction. The results indicate that the consistent implementation of teaching ethics is essential for mathematics teachers and requires sustained effort. By regularly applying the recommended ethical practices, mathematics teachers can become more adept at conducting the teaching and learning process in accordance with professional ethical standards, thus fostering a positive learning environment for students.